Características do apoio social e capacidade funcional de idosos assistidos em unidades de atenção básica no municipio de Lins: estudo epidemiológico para implantação de serviço - Pizzighini, Rosangela Badine [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
To evaluate the independence level as well as psychosocial and health-related aspects of elders attended to by the primary health care network in Lins and to indentify factors associated with the presence of aggravations in these domains. This is a cross-sectional epidemiological study involving a random sample selected among 6,766 older individuals registered in the city’s primary health care units in 2008. Socioeconomic (schooling, family income, social class) and demographic (gender, age, marital status, and household arrangement) data were collected. They were used to characterize the sample and their association with the elders’ health parameters. The situation of dependence to perform basic and instrumental activities of daily living was evaluated by the ADL (Katz, et al., 1983) and IADL (Lawton et al., 1969) scales, respectively. The following were also evaluated: cognitive capacity by the Mini-Mental State Examination (MMSE), categorized according to Bertollucci (1998), functional capacity by the Pheffer Questionnaire for Functional Evaluation (PQFE) (1982), presence of depression by GDS-15 (Yesavage, et al., 1983), self-perception of health (excellent, very good, fair, bad and very bad) and indicators of social support availability by applying a questionnaire validated for Brazil by Chor et al. (2001). Data collection, from September to December, was conducted by trained interviewers (five nurses and 109 community health agents) in the respondents’ homes, at a previously schedules time and in a place that would ensure the elders’ privacy. The following are noteworthy as the elders’ main characteristics: almost half of them were 60 to 69 years old (47.0%); 63.4% were females; 53.3% were married or had common-law partners; 18.6% lived alone; 21.9% were illiterate and 68.5% had attended school for up to three years; 90% were classified as belonging to socioeconomic ... (Complete abstract click electronic access below)
Keywords: Cuidados primários de saúde; Saude mental; Idosos - Saúde; Cognitive capacity; Functional capacity